The Influence of Public Financial Input on the development of regional cultural industry: A case study of Tibet - Rendan, Caiwang (2020)
This dissertation adopts the statistical data of Tibet Autonomous Region, DEA model, VAR model and other methods to evaluate the performance of public investment on the development of cultural industry in Tibet Autonomous Region from the horizontal and vertical perspectives, predicts the development of cultural industry until 2030, and finally puts forward policy Suggestions based on the conclusions. The main conclusions of this dissertation are as follows: 1. The operating surplus of the cultural industry in Tibet Autonomous Region accounts for a fair proportion of the total output, which has a certain basis for progress. However, input-output efficiency and consumption scale and growth rate are at a low level nationwide.2. Uneven development of the cultural industry in Tibet autonomous Region, with weak cultural manufacturing and developed tourism;Fiscal cultural expenditure has an inhibitory effect on per capital cultural consumption of residents in the region, but has a significant promotion effect on tourism income, and cultural consumption and tourism income have a synergistic effect. 3. The public investment in Tibet Autonomous Region is not good, with excessive input in terms of the number of cultural institutions and financial input, and the structure is seriously unbalanced; But benefit from the small size of the population, per capital fiscal cultural expenditure level is not low. Therefore, this dissertation puts forward that we should focus on improving the infrastructure in the region, optimize the fiscal expenditure structure, pay attention to the promoting role of cultural consumption in the cultural industry, actively explore the domestic and foreign markets, and enhance the performance of financial support for the development of cultural industry.